A SIMULATION LANGUAGE COMPILER BASED MODELING AND SIMULATION FRAMEWORK - Song, Xiao; Ji, Hang; Tang, Wenjie; Zhang, Xing; Xiao, Zhen (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
It is important yet difficult to develop a multi-function simulation framework which provides simulation language specification, compiler transferring language script to simulation components, simulation engine etc. To provide simulationists a useful multi-function framework, we develop a simulation language compiler based modeling and simulation framework, i.e., a simulation tool named SimRunner. This tool is capable of building simulation language based models, compiling language to simulation models, establishing interactive network communications with distributed simulation engines, controlling and supervising simulation conditions. A use case of anti-air simulation is implemented with this framework, which is validated to have useful functions and be stable with running distributed models.